Search for maximal flavor violating scalars in same-charge lepton pairs in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2009)
Models of maximal flavor violation (MxFV) in elementary particle physics may contain at least one new scalar SU(2) doublet field ΦFV=(η0,η+) that couples the first and third generation quarks (q1, q3) via a Lagrangian term LFV=ξ13ΦFVq1q3. These models have a distinctive signature of same-charge top-quark pairs and evade flavor-changing limits from meson mixing measurements. Data corresponding to 2fb-1 collected by the Collider Dectector at Fermilab II detector in pp̄ collisions at s=1.96TeV are analyzed for evidence of the MxFV signature. For a neutral scalar η0 with mη0=200GeV/c2 and coupling ξ13=1, ∼11 signal events are expected over a background of 2.1±1.8 events. Three events are observed in the data, consistent with background expectations, and limits are set on the coupling ξ13 for mη0=180-300GeV/c2. © 2009 The American Physical Society.